Nutrient-rich, high-quality, protein-containing dairy foods in combination with exercise in aging persons to mitigate sarcopenia - Phillips, Stuart M; Martinson, Wendy (Nutrition reviews, 2019)
Abstract Sarcopenic declines in muscle mass and function contribute to the risk of falls, reduced mobility, and progression to frailty in older persons. Mitigation of sarcopenia can be achieved by consumption of higher quality protein in sufficient quantities, which current research suggests are greater than the recommended intakes of approximately 0.8 g/kg bodyweight/d. In addition, higher levels of physical activity and participation in exercise to support cardiovascular fitness and musculoskeletal function work additively with protein in attenuating sarcopenia. This narrative review provides evidence to support a recommendation for per-meal protein targets in older persons that are underpinned by knowledge of muscle protein turnover. Based on work examining acute dose–responses of muscle protein synthesis (MPS) to protein, a proposed per-meal target for protein intakes is set at approximately 0.4–0.6 g protein/kg bodyweight/meal for older persons. Habitual patterns of dietary protein intake tend to emphasize a skewed protein distribution, which would not maximize muscle anabolism. Observational studies show that more even patterns of protein intake are associated with increased muscle mass and improved muscle function. A food-based approach to achieving these protein targets would be advantageous, and the nutrient density of the protein-containing foods would be particularly important for older persons. Dairy foods provide high-quality protein and contain several nutrients of concern for older persons. This brief review provides an overview of the science underpinning why dairy foods should be a point of nutritional emphasis for older persons. Practical suggestions are provided for implementation of dairy foods into dietary patterns to meet the protein and other nutrient targets for older persons.